The Effect of Physical Work Environment and Work Discipline on Employee Performance at the Polyurethane Department of PT Pratama Abadi Industri in Serpong - Fathan Arif; Tantri Tantri; Denok Sunarsi (International Journal of Education, Information Technology, and Others, 2023)
This study aims to determine the Effect of Physical Work Environment and Work Discipline on Employee Performance at the Polyurethane Department of PT Pratama Abadi Industri in Serpong either partially or simultaneously. This type of research uses descriptive quantitative methods. The sampling technique uses a saturated sample of 54 respondents. Data analysis techniques using, data instrument test, classic assumption test, simple linear regression, multiple linear regression, correlation coefficient, and coefficient of determination. Test the hypothesis using the t-test and F-test. The results of the analysis show: Physical Work Environment partially affects employee performance with a simple linear regression equation Y = 8.609 + 1.014X1. The correlation coefficient value is 0.807 meaning that it has a strong relationship level and a determination coefficient of 0.651 means that performance is influenced by the Physical Work Environment by 65.1%. This is evidenced by the t-test obtained t count > t table (9.857 > 2.00758) and reinforced by a significant value <0.05 (0.000 <0.05). Work Discipline partially has a positive effect on employee performance, shown by the simple linear regression equation Y = 0.786 + 0.977X2. The correlation coefficient value is 0.926, meaning that it has a strong relationship, and a determination coefficient of 0.860 means that competence influences performance by 86%. This is evidenced by the t-test obtained t count > t table (17.838 > 2.00758) and reinforced by a significance value <0.05 (0.000 <0.05). The results of the study of the Physical Work Environment and Work Discipline simultaneously on employee performance are shown by the multiple linear regression equation Y = 1.003 + 0.194 X1 + 0.844 X2, the correlation coefficient value is 0.931 meaning that it has a strong relationship level and the determination coefficient is 0.867%, meaning that performance is influenced by Work Environment and Work Discipline of 86.7%. This is evidenced by the results of the F-test hypothesis test obtained by F count > F table (166.392 > 3.18) and reinforced by a significance value <0.05 (0.000 <0.05). Thus it is proven that Ho is rejected and Ha is accepted.